IDENTIFICATION OF STEM RUST RESISTANCE SOURCES IN WHEAT BY USING MOLECULAR MARKERS - A. M. Kokhmetova; M. N. Atishova (Вавиловский журнал генетики и селекции)
Puccinia graminis f. sp. tritici induces stem rust, which is the cause of a considerable crop loss. Race Ug99 of P. graminis f. sp. tritici (pathotype TTKS) is virulent to the majority of wheat varieties. According to FAO reports, major wheat-producing countries to the east of Iran (Afghanistan, India, Pakistan, Turkmenistan, Uzbekistan and Kazakhstan) are greatly endangered. It is necessary to seek resistance sources to stem rust with identified Sr genes. Screening with PCR SSR and STS markers associated with effective Sr genes (Sr2, Sr22, Sr24 and Sr46) was undertaken to identify Sr gene sources. Twelve accessions with the Sr2-gene were identified. Seven resistant lines were found to possess Sr24/Lr24 genes. Sr46 was identified in one line. PCR analysis revealed the presence of Sr22 in six promising lines. The results are used in wheat breeding programs for stem rust resistance with marker-assisted selection.